Anatomical pre-contoured plates in management of distal tibia fracture: a prospective study - Laik, Jayanta K.; Niraj, Nishant K.; Kaushal, Ravi; Kumar, Ritesh; Sarkar, Somit (International Journal of Research in Orthopaedics, 2023)
Background: Distal tibial fractures are complex injuries with high complication rate. Management of such fractures are often complicated by soft tissue injuries. Precarious vascularity around distal tibia also results in high non-union rates. This study aims to study and analyse the outcome of distal tibia fracture managed by anatomical contoured plate. Methods: In this prospective observational study, we attempted to assess the functional and radiological outcome of distal tibia fracture managed by with distal tibia fracture with average follow up of 24 weeks. ORIF/MIPO with plating was done for fracture distal tibia with anatomical precontoured plates. Results: Patients were evaluated using AOFAS and measure of ankle range of motion. Average functional score was 88 with complications in 3 patients. Conclusions: We believe precontoured plates provide for better biological fixation than conventional plates.